Fatal correlation between YAP1 expression and glioma aggressiveness: clinical and molecular evidence. Issue 2 (28th August 2018) - Guichet, Pierre‐Olivier; Masliantsev, Konstantin; Tachon, Gaëlle; Petropoulos, Christos; Godet, Julie; Larrieu, Delphine; Milin, Serge; Wager, Michel; Karayan‐Tapon, Lucie
Abstract: During the last decade, large‐scale genomic analyses have clarified the somatic alterations in gliomas, providing new molecular classification based on IDH1/2 mutations and 1p19q codeletion with more accurate patient prognostication. The Hippo pathway downstream effectors, YAP1 and TAZ, have recently emerged as major determinants of malignancy by inducing proliferation, chemoresistance, and metastasis in solid tumors. In this study, we investigated the expression of YAP1 in 117 clinical samples of glioma described according to the WHO 2016 classification. We showed for the first time that YAP1 was tightly associated with glioma molecular subtypes and patient outcome. We validated our results in an independent cohort from the TCGA database. More interestingly, we found that YAP1 may have prognostic significance for predicting patient survival, especially in low‐grade gliomas. Using patient‐derived glioblastoma stem cell cultures, we demonstrated that YAP1 was activated and that it controlled cell proliferation. Transcriptome analysis revealed lower expression of YAP1 in the proneural GBM subtype. Furthermore, we found that overexpression of YAP1 was sufficient to inhibit the OLIG2 proneural marker, suggesting its involvement in maintenance of the GBM phenotype. Taken together, our results showed that YAP1 could be a relevant prognostic biomarker and a potential therapeutic target in glioma. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.